SOSIALISASI UPDATING DATA PUBLONS, RESEARCHER ID, ORCID DALAM MENDUKUNG PEMERINGKATAN SINTA UNIVERSITAS - Baharudin, Erwan; Ernawati, Ernawati; Cahyadi, Lukman; Mulyani, Erry Yudhya (Universitas Esa Unggul, 2021)
Lecturers' activities in addition to teaching, researching and conducting community activities, must also publish the results of research and community service in journals and proceedings. It aims to find out whether the article is read or quoted by other people. To find out if our writing is quoted by others, it takes several ID accounts that support the publication in Sinta. The more our articles are cited, the higher the university ranking will be. Currently, the Ministry of Education and Culture urges lecturers to update the ID publons, researcher ID, Orcid, and Garuda because the current version 2 sinta system will be migrated to the latest version, namely version 3. However, many lecturers do not know and do not understand how how to update existing data in Sinta. The purpose of this community service is to provide knowledge and willingness of lecturers to update the ID supporting publications. The method of implementing this activity uses a zoom application with a capacity of 100 participants and the material is in the form of a power point slide. The result of this community activity is the updating of supporting ID for lecturer publications and increasing the knowledge of lecturers in updating data. The conclusion of this activity is that the lecturers at Esa Unggul University have updated the ID data supporting their respective publications in accordance with the recommendations of the Ministry of Education and Culture in the context of migrating the Sinta system version 2 to version 3.Keywords : Updating data, data migration, university ranking